Buckling performance of co‐cured and stiffened composite structure with embedded multilayer damping membranes. Issue 10 (30th June 2022) - Wang, Shaoqing; Zhang, Junling; Guo, Anfu; Liang, Sen
Abstract: This research aims to explore the buckling performance of a co‐cured and stiffened composite structure with embedded multilayer damping membranes (CSCSEMDM) under static load. A buckling model of this structure is established theoretically by using the principle of minimum potential energy and first‐order shear deformation theory. Then, the governing equation of the structure is obtained. The critical buckling load of the structure is solved, and the finite element method is used to verify the correctness of the theoretical model and theoretical methods. Finally, the effects of various parameters on the critical buckling load are discussed on the basis of the validated model. Abstract :